2019
DOI: 10.1055/s-0039-1687822
|View full text |Cite
|
Sign up to set email alerts
|

Homeopathy as Therapy for Mycosis Fungoides: Case Reports of Three Patients

Abstract: Background Mycosis fungoides (MF) is an uncommon, indolent, form of cutaneous T cell lymphoma, of which there are various types according to international classification. Various treatment modalities are available; however, these are fraught with potentially severe adverse effects. Methods Three cases of immunohistochemically confirmed MF were treated with classical individualized homeopathy. Each case was followed up with photographic documentation and was reported according to the criteria set ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In homoeopathy, many studies were found where improvement in the quality of life, as well as remission of skin patches of psoriasis, has been evident. 14 22 23 24 25 38 In this case, different validated scales (ORIDL, PASI and PDI) were used to assess the improvement. On every follow-up visit, physician, as well as the patient's assessed response, went toward ‘positive (+)’ in ORIDL scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In homoeopathy, many studies were found where improvement in the quality of life, as well as remission of skin patches of psoriasis, has been evident. 14 22 23 24 25 38 In this case, different validated scales (ORIDL, PASI and PDI) were used to assess the improvement. On every follow-up visit, physician, as well as the patient's assessed response, went toward ‘positive (+)’ in ORIDL scale.…”
Section: Discussionmentioning
confidence: 99%
“…16 17 Related literature of psoriasis in homoeopathy is voluminous 18 19 20 21 in nature and ample studies documented favouring homoeopathy are available. 14 22 23 24 25 This case of psoriasis documented through standard and validated scales along with the objective evidence in the form of photographs showed. Rapid and gentle improvement within 2 months with substantial relief physically and psychologically.…”
Section: Introductionmentioning
confidence: 99%
“…These nanomolecules may further influence physiological processes in the human body ( 14 ). Previous case reports and case series suggested that homeopathy could be useful in a wide variety of cutaneous disorders, including acne ( 15 , 16 ), psoriasis ( 17 ), recalcitrant generalized lichen planus ( 18 ) and cutaneous lymphoma ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The homeopathic pharmacopoeia includes many drugs that have an action predominantly on the skin 10 , and many disparate conditions have shown excellent response clinically to them [11][12][13][14] . Nwabudike in 2016 published a homeopathic case report of impetigo in an elderly man 15 who benefited from a different homeopathic medicine, Hepar sulphuricum.…”
Section: Discussionmentioning
confidence: 99%